Involuntary Terminations, Unemployment, and Job Matching: A Test of Job Search Theory - Gottschalk, Peter; Maloney, Tim (Journal of Labor Economics, 1985)
We develop a search model that focuses on the expected result of search. The model focuses on four conceptually different steps which are taken in changing jobs. First, the person is either voluntarily or involuntarily terminated. Second, the person who decides to quit (or who is involuntarily terminated with prior notification) chooses whether to search on the job or full time (i.e., by becoming unemployed). Third, as each job offer is received, the person decides either to accept it or to continue searching for a better offer. The fourth step occurs after the person has evaluated the "experience-good" aspects of the job. At that point he or she can determine whether the new job is better than the previous job. The question we ask is whether the type of termination and/or the experience of unemployment affects the probability that the person will find the new job preferable to the previous job. The model predicts that the type of termination will affect the probability of moving to a better job but the experience of unemployment will not. This prediction is verified using 1978-79 data from the PSID to estimate a bivariate probit model.